Green composites for aircraft interior panels. (2017) - Scarponi, Claudio; Santulli, Carlo; Sarasini, Fabrizio; Tirillò, Jacopo
In recent years, a rapid growth in the research and innovation in the natural fibre composites (NFCs) sector has been experienced. The application of NFCs can in principle reduce environmental impact of synthetic fibre composites, such as fibreglass, mainly because of the renewable nature of fibres of vegetable origin. Costs would not be excessive especially in the case the fibres are a part of a large productive system, which includes other products with significant added value. Research is therefore concentrated on improving the mechanical performance of NFCs to extend their capabilities and fields of application. In this sense, entering the aeronautical sector is an ambitious, yet possibly realistic objective. However, fibre selection involves a number of aspects, including textile properties and agronomic origin of the reinforcements. The assessment of their compatibility with polymer matrices used in aviation needs also considering the issues related to fibre treatment. Specific topics are also related to aspects crucial for operation into aircraft, such as flammability and resistance to impact loading. This study provides a bibliographic review in the broad field of green composites showing the potential of their application in the near future in production of aircraft interior panels.